Strategy, corporate culture, structure and operational processes as the context for the innovativeness of an organization - Katarzyna Szczepańska-Woszczyna (Foundations of Management, 2018)
The paper refers to relationships between the innovativeness of an organization and its selected determinants such as strategy, corporate culture, structure and operational processes. Research was conducted among 200 managers at the top, middle and operational levels of management (200 companies operating in Poland implementing innovations - innovative companies). Conditions leading to innovations are described as the combination of processes, which result from the internal and external dynamics of a given entity. The analysis assumed that the assessment of company innovativeness would be based on an assessment of whether the company is a leader in the industry in terms of new products (the higher the rating, the more innovative the company is considered to be). The relationship between the dimensions of the company's functioning and the degree of its innovativeness was rated on the basis of two measures: the Spearman's rank correlation coefficient and the chi-square coefficient. It was assumed that the most innovative companies have structures similar to organic ones, with a weak influence of the elements of mechanistic structures. This assumption was proven in relation to features of organizations considered important for innovativeness.
Keywords: L21; M14; O31; 650; innovation; innovativeness; strategy; structure; corporate culture; operational processes; innovation determinants